WASTES : solutions, treatments and opportunities II : selected papers from the 4th edition of the International Conference on WASTES : solutions, treatments and opportunities, Porto, Portugal, 25-26 September 2017 - WASTES : solutions, treatments and opportunities (2017 : Porto, Portugal); Castro, Fernando; Lurdes Lopes, Maria de; Vilarinho, Candida (Boca Raton, FL : CRC Press, 2018)
"This volume presents a selection of papers from the WASTES 2017 conference, a platform for scientists and industries from the waste management and recycling sectors from around the world, who shared experiences and knowledge at the meeting. Covering discussions regarding the balance between economic, environmental and social outcomes, the development of innovative techniques, tools and strategies on how wastes can be transformed into good ideas. Improving both the overall environmental performance and the understanding of the industry impact on the environment, as well as the options analysis for its improvement were key objectives of this conference."--Provided by publisher.
Includes bibliographical references and index.
Also available in print format.
Keywords: Refuse and refuse disposal -- Environmental aspects; Refuse and refuse disposal; Waste minimization; Electronic books